A history of biology - Morange, Michel (Princeton University Press, 2021)
"This book presents a complete, global history of the biological sciences from ancient times to today-introducing a long-term perspective to the history of biological thought, while showing its fractures and upheavals through the ages. The history of biology often neglects certain areas, such as ecology, ethology (the study of non-human animal behavior), and plant biology-areas which are covered in this work. The broad, global perspective offered here will allow the reader to better appreciate the nature of the interdisciplinary exchanges that have shaped the biological sciences, perhaps more than any other discipline. Much attention is also given to the contribution of technology, the role of experimentation, and, more generally, the social and technological environment within which scientific transformations develop"--